Novel Numerical Characterization of Protein Sequences Based on Individual Amino Acid and Its Application. (2nd February 2015) - Zhang, Yan-ping; Sheng, Ya-jun; Zheng, Wei; He, Ping-an; Ruan, Ji-shuo
Abstract : The hydrophobicity and hydrophilicity of amino acids play a very important role in protein folding and its interaction with the environment and other molecules, as well as its catalytic mechanism. Based on the two physicochemical indexes, a 2D graphical representation of protein sequences is introduced; meanwhile, a new numerical characteristic has been proposed to compute the distance of different sequences for analysis of sequence similarity/dissimilarity on the basis of this graphical representation. Furthermore, we apply the new distance in the similarities/dissimilarities of ND5 proteins of nine species and predict the four major classes based on the dataset containing 639 domains. The results show that the method is simple and effective.